FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK PELAYANAN ANTENATAL CARE TERPADU PADA BIDAN DI PUSKESMAS COLOMADU - Anisa Nur Cahyanti; Atik Mawarni; Sri Winarni; Cahya Tri Purnami (Jurnal Kesehatan Masyarakat, 2023)
Visits of pregnant women during the Covid 19 pandemic at the Colomadu Health Center has decreased by 20%, visits before the pandemic could reach 100% and decreased to 80% during the pandemic. The decrease in visits was caused by the anxiety of pregnant women about the transmission of the virus and the unstandardized Integrated ANC (Antenatal care) services by the midwives. Midwives did not provide counseling, hand and foot examinations, and breast examinations. The purpose of this study is to analyze the relationship between age, knowledge, attitudes, and motivation with the practice of the Integrated ANC services for midwives at the Colomadu  Health Center. This study was an observational study with a cross-sectional design. The research sample used a purposive sampling technique, namely 14 midwives. Data analysis uses Pearson correlation test. The result showed that age (p-value=0.006), knowledge (p-value=0.0001), attitude (p-value=0.004), and motivation (p-value=0.009) were related to the practice of the Integrated ANC services. The factor that has the highest correlation coefficient was knowledge (r=0.853). This study concludes that there is a significant relationship between age, knowledge, attitude, and motivation with the practice of the Integrated ANC services.